ASSESSMENT OF CARDIAC OUTPUT AND STROKE VOLUME IN CRITICALLY ILL ADULT PATIENTS BY TRANSTHORACIC ECHOCARDIOGRAPHY AND PULSE INDEX CONTINUOUS CARDIAC OUTPUT MONITOR - HAROON , M; SULAIMAN, .; KHAN , MJ; HAQ , IU; AHMAD , S; FARID , K; IQBAL , MN (Biological and Clinical Sciences Research Journal, 2024)
Accurate measurement of cardiac output (CO) and stroke volume (SV) is crucial for the management of critically ill patients. While transthoracic echocardiography (TTE) is a well-established method, pulse index continuous cardiac output (PiCCO) monitoring is gaining attention for its potential advantages in constant hemodynamic monitoring. Objective: To compare cardiac output and stroke volume assessments derived from transthoracic echocardiography (TTE) and pulse index continuous cardiac output monitoring (PiCCO) in critically ill adult patients. Methods: This prospective comparative study was conducted at Khyber Teaching Hospital from May 2022 to November 2022, following ethical approval from the institutional review board. A cohort of 25 adult patients of both genders, requiring hemodynamic monitoring as per clinical indications, was included through non-probability consecutive sampling. Both TTE and PiCCO were performed to measure cardiac output and stroke volume. Pearson correlation and Bland-Altman plots were utilized to analyze the outcomes statistically. Results: The comparison revealed a non-significant positive correlation between CO values obtained via TTE and PiCCO (P=0.434, r=0.164) and a significant positive correlation for cardiac index (CI) values (P=0.010, r=0.506). Conversely, a non-significant negative correlation was observed for SV values (P=0.45, r=-0.158). The mean differences for CO, CI, and SV between TTE and PiCCO were 0.214 L/min, -0.0056 L/min, and -1.292 L/min, respectively, with varying confidence intervals across the measurements. Conclusion: The measurements of cardiac output and stroke volume obtained from transthoracic echocardiography were comparable to those obtained via PiCCO. These findings support the reliability of echocardiography for assessing hemodynamic parameters in critically ill patients.